2016
DOI: 10.1021/acs.orglett.6b01355
|View full text |Cite
|
Sign up to set email alerts
|

Toward Leiodermatolide: Synthesis of the Core Structure

Abstract: The macrocyclic core (35) of the marine natural product leiodermatolide (1) was synthesized from two key fragments, vinyl iodide 23 (C1-C11 part) and vinyl stannane 31 (C12-C18 part). A Stille coupling led to conjugated Z,Z-diene 32. The derived seco acid 34 was cyclized using a Yamaguchi macrolactonization. Key steps in the assembly of vinyl iodide 23 were a Paterson aldol reaction, and a Kumada coupling on a triflate derivative to create the C4-C5 trisubstituted double bond. The two stereocenters in fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…[21] In 2016, they subsequently reported the construction of am acrocyclic core with the required revision to the stereochemistry. [22] In 2012, the Fürstner group disclosedacompleted synthesis of both candidate diastereomers corresponding to our published structure 5 of (À)-leiodermatolide. [23] Careful 1 HN MR comparison showed that the compound with the diastereomeric side chain was distinguishable by minor differences in peak shape,w hile the NMR data for 5 exactly matched that obtainedf or leiodermatolide.C orrelation of the optical rotation also confirmed that structure 5 represents the naturale nantiomer.…”
Section: Synthetic Effortstowards Leiodermatolidementioning
confidence: 99%
See 1 more Smart Citation
“…[21] In 2016, they subsequently reported the construction of am acrocyclic core with the required revision to the stereochemistry. [22] In 2012, the Fürstner group disclosedacompleted synthesis of both candidate diastereomers corresponding to our published structure 5 of (À)-leiodermatolide. [23] Careful 1 HN MR comparison showed that the compound with the diastereomeric side chain was distinguishable by minor differences in peak shape,w hile the NMR data for 5 exactly matched that obtainedf or leiodermatolide.C orrelation of the optical rotation also confirmed that structure 5 represents the naturale nantiomer.…”
Section: Synthetic Effortstowards Leiodermatolidementioning
confidence: 99%
“…They first reported a synthesis of several fragments, including a diastereomeric macrocyclic core, epimeric at the two methyl‐bearing stereocentres at C8 and C10 relative to those assigned in structure 5 . In 2016, they subsequently reported the construction of a macrocyclic core with the required revision to the stereochemistry …”
Section: Introductionmentioning
confidence: 99%
“…First, vinyl iodide 21 was prepared from known alkynediol 18 via silylation to bis‐silyl ether 19 , iodination of the alkyne function to give iodoalkyne 20 and diimide reduction resulting in Z ‐vinyl iodide 21 in good overall yield (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Some years ago our group described the synthesis of key fragments for the C6,C8‐epimer and the synthesis of a corresponding macrolactone core . Quite recently, we completed a synthesis of the macrolactone core 13 with the correct stereochemistry . Here the two fragments 10 and 11 were combined via Stille coupling (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…C-Sn bond is known as a kind of very important carbon-metal bond, which has numerous applications in organic chemistry 1 , 2 , biological chemistry 3 5 , and medicinal chemistry 6 , 7 . There are three main routes for the transformation of organostannanes, including transmetalation process 8 10 , carbanion process 11 , and radical process 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%